The Fashion Retail and the value creation with sustainable products: a multiple case study (ModaPalavra e-periódico, 2016)
This study aims to understand how the development of sustainable products in Brazilian fashion retail businesses creates value for the companies themselves, society and the environment. A qualitative approach to multiple case study method investigates practices and processes at four companies from Rio de Janeiro State. The study collected primary information from direct observation and interviews with the firms’ directors, and secondary data from industry reports and other documents. Three overall dimensions of the study -environmental management, value creation and product development in fast fashion companies -encoded into seven categories, when considered in data cross-synthesis, elucidate the following conclusions: (1) the firms do not have economic, ethical and legal fields integrated view; (2) the companies do not believe that the fashion consumer market values environmental practices and thus not motivated to invest in practices and products; (3) a fragmented supply chain makes it difficult to control activities and appears as a major constraint to the development of sustainable products; (4) access to information on best environmental practices and tax incentives are important inductors’ mechanisms to leverage the development of sustainable products in the Brazilian fashion retail; (5) the development of strategic capabilities in pollution prevention area, management products and clean technology create value for the production chain.
Keywords: fashion; fast fashion; value creation; sustainable products